2003
DOI: 10.1007/s00572-003-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of seedlings of native plants in an impoverished and highly disturbed soil following inoculation with arbuscular mycorrhizal fungi

Abstract: We investigated whether arbuscular mycorrhizas influenced growth and survival of seedlings in an extremely impoverished and highly disturbed soil. Seedlings of four plants species native to the site were either inoculated with native sporocarpic arbuscular mycorrhizal (AM) fungi or fertilised prior to transplanting, and followed over 86 weeks at the site. One treatment was also irrigated with N-rich leachate from the site. In a laboratory experiment, seedlings were fertilised with excess P for 6 weeks, and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Curlevski et al. (2009) found identical fungal genotypes in roots of Epacris pulchella , an Australian species forming ericoid mycorrhizas, and Leptospermum polygalifolium (Myrtaceae) which has been reported to form both ECM and arbuscular mycorrhizal associations (Pattinson et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Curlevski et al. (2009) found identical fungal genotypes in roots of Epacris pulchella , an Australian species forming ericoid mycorrhizas, and Leptospermum polygalifolium (Myrtaceae) which has been reported to form both ECM and arbuscular mycorrhizal associations (Pattinson et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of arbuscular mycorrhiza may therefore be an important growth strategy for wild forage plants in the natural semi-arid steppe ecosystems of eastern Inner Mongolia. Moreover, arbuscular mycorrhizal associations also provide an important approach for promoting seedling establishment [28]. However, to our knowledge information on the arbuscular mycorrhizal status of wild forage plants in the steppe is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of efficient AM fungi is usually considered as a prerequisite to inoculation programs as the efficiency of mycorrhizal inoculation on the plant growth depends on the species involved (Roldan et al 1992;Herrera et al 1993;Duponnois et al 2001b). It has been shown that survival rates and early growth performance of various softwood and hardwood species was significantly improved in the field after specific AM fungal inoculation (Mosse et al 1982;Herrera et al 1993;Jasper 1994;Caravaca et al 2003;Pattinson et al 2004). However, inoculation of plants with AM fungi still only occurs at a small scale in revegetation schemes and few studies have clearly demonstrated the benefits of fungal inoculation in the field.…”
Section: Introductionmentioning
confidence: 99%